Pair neutrino energy loss for nuclei 56^Fe at the late stages of stellar evolution - 刘晶晶 罗志全 (Chinese physics C, 2008)
t Based on the Weinberg-Salam theory, the pair neutrino energy loss rates for nuclei 56^Fe are canvassed for the wide range of density and temperature. The results of ours （QLJ） are compared with those ofBeaudet G, Petrosian V and Salpeter E. E＇s （QBPs）, and it shows that the pair neutrino energy loss rates of QBPS are always larger than QLJ .The QBPS is 12.57%, 12.86%, 14.99%, 19.80% times higher than QLJ corresponding to the temperature T9=0.385, 1.0, 5.0, 10, respectively.